Ne partecipavano indiferentemente poveri et richi. Patronage, community cohesion and distinction among the needy: indigence and hospitals in northern Lombardy between the Late Middle Ages and the Early Modern Age. (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
This essay deals with hospitals and the various forms of solidarity related to the communities in pre-alpine and alpine Lombardy during the time between the Later Middle Ages and the Early Modern Age. This field of institutions, along with its culture of piety, appears to have been intensely competitive: it involved opposing jurisdictional claims and different ideal and practical orientations, which highlighted deep historical discontinuities. In fact, the polemics against what were considered “abuses”, a category that should be considered more critically, had a decisive weight, because the practices of competitors in controlling the material and symbolic resources of almsgiving are often denigrated by one side or the other as abuses. The late medieval panorama, essentially characterized by the random distribution of food and wine, was later profoundly transformed, with the foundation of mounts of piety, the consolidation and sometimes the upgrading of hospitals, thanks to the initiatives of the communities themselves. However, the overcoming of some manifestations of traditional piety was also due to the consequence of the interference of the various social and institutional actors – individuals, communities, state and ecclesiastical authorities – and above all to the pressures from the latter. In fact, there were many possible forms of generosity: aristocratic clientelism, festivals of collective cohesion to which the poor and others flocked to have food and drink, the tendency of the community to grant land and loans renouncing any formal control of these resources. Just as the communities had degraded aristocratic liberality to a mere particularistic affair, the Church was more than ready to denounce the waste of ceremonial charity, promoting the delimitation of the ‘real poor’ as a group, to whom to allocate resources through a more rigorous management. However, ecclesiastical control over pious grants also encountered a local sensitivity of rigorist milieus and resulted in more general effects, in the abandonment of a charity without measure, and in the promotion of more analytical models of social distinction.
Keywords: Charity; jurisdictional conflict; administrative misdeeds; feast; collective identity